Genetic Distances Within-Population and Between-Population of Tonguesole, Cynoglossus spp. Identified by PCR Technique - Yoon, Jong-Man (Dev Reprod, 2019)
The higher fragment sizes (>2,100 bp) are not observed in the two C. spp. populations. The six oligonucleotides primers OPA-11, OPB-09, OPB-14, OPB-20, OPC-14, and OPC-18 were used to generate the unique shared loci to each tonguesole population and shared loci by the two tonguesole populations. The hierarchical polar dendrogram indicates two main clusters: Gunsan (GUNSAN 01–GUNSAN 11) and the Atlantic (ATLANTIC 12–ATLANTIC 22) from two geographic populations of tonguesoles. The shortest genetic distance displaying significant molecular difference was between individuals’ GUNSAN no. 02–GUNSAN no. 01 (genetic distance=0.038). In the long run, individual no. 02 of the ATLANTIC tonguesole was most distantly related to GUNSAN no. 06 (genetic distance=0.958). These results demonstrate that the Gunsan tonguesole population is genetically different from the Atlantic tonguesole population. The potential of PCR analysis to identify diagnostic markers for the identification of two tonguesole populations has been demonstrated. As a rule, using various oligonucleotides primers, this PCR method has been applied to identify polymorphic/specific markers particular to species and geographical population, as well as genetic diversity/polymorphism in diverse species of organisms.